2003
DOI: 10.1073/pnas.1936024100
|View full text |Cite
|
Sign up to set email alerts
|

A proatherogenic role for cGMP-dependent protein kinase in vascular smooth muscle cells

Abstract: Nitric oxide (NO) exerts both antiatherogenic and proatherogenic effects, but the cellular and molecular mechanisms that contribute to modulation of atherosclerosis by NO are not understood completely. The cGMP-dependent protein kinase I (cGKI) is a potential mediator of NO signaling in vascular smooth muscle cells (SMCs). Postnatal ablation of cGKI selectively in the SMCs of mice reduced atherosclerotic lesion area, demonstrating that smooth muscle cGKI promotes atherogenesis. Cell-fate mapping indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 50 publications
8
72
0
Order By: Relevance
“…These observations identify a function of cGKI signaling in the regulation of erythrocyte survival and support the emerging concept that pathways via NO, cGMP, and cGKI stimulate growth and survival in a number of cell types in vivo (55)(56)(57)(58).…”
Section: Figsupporting
confidence: 74%
“…These observations identify a function of cGKI signaling in the regulation of erythrocyte survival and support the emerging concept that pathways via NO, cGMP, and cGKI stimulate growth and survival in a number of cell types in vivo (55)(56)(57)(58).…”
Section: Figsupporting
confidence: 74%
“…cell number, relative cell number. (31)(32)(33). Therefore, it was tested whether Rp-PET could inhibit cGMP/cGKI-stimulated VSMC growth and phosphorylation of VASP.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies have shown that NO promotes Akt phosphorylation via cGMP production in vascular smooth muscle cells (26), which could provide a link between shear stress on the endothelium and Akt phosphorylation in smooth muscle. Abolishing NO production by L-NAME caused decreased Akt phosphorylation in WT but not KO portal veins, despite a probably higher NO production in KO portal veins.…”
Section: Discussionmentioning
confidence: 99%